Vrhunski sport - Mićović, Miodrag (Array, 2018)
The concept of high-level sport, which is based on providing support to achieve top results, began to develop in the second half of the last century. In some countries, high-level sport is based on the financial support that the state provides to top-class athletes, while others combine financial support with other measures to facilitate athletes engaged in sports or other related activities. In this regard, article deals with the issues concerning: the basic principles of high-level sport; conditions for acquiring the status of top-class athlete; effects resulting from the status of top-class athlete; the basis for the loss of rights of top-class athlete.